Research in the Field of Obtaining Activated Alumina. Part 6. Effect of Complex Additive on Reactive Alumina Production Technology and Properties of Alumina Based Low-Cement Refractory Castables - Trubitsyn, M. A.; Volovicheva, N. A.; Furda, L. V.; Lisnyak, V. V.; Kurbatov, A. P.; Tarasov, I. A.; Bondareva, I. A. (Refractories and industrial ceramics, 2024)
Results of studying the process of producing reactive alumina in the presence of a complex additive, including polycarboxylate ester (PCE) and polyethylene glycol (PEG), are presented. The effect of such reactive alumina on rheotechnological properties of matrix systems and low-cement refractory castables is evaluated. The synergetic effect of combined introduction of PEG and PCE during fine milling of raw alumina is established. It is shown that the deflocculating effect of polycarboxylate ester and the intensity of the milling process are strengthened.